Careers of Swedish professional handball players: From an empirical model to career-long psychological support services - Ekengren, J. (2020)
This PhD Project with a specialization in sport psychology is inspired by the cultural praxis of athletes` careers paradigm. This implies that the Project blends theory, research, and practice within the context of Swedish handball, by investigating career pathways of professional players providing empirically based, and context specific, implications. The overarching aim of the Project is twofold: (a) to examine the career experiences of Swedish professional handball players and consolidate them into the empirical career model of Swedish professional handball players (ECM-H), and (b) based on the ECM-H, to develop, validate, and test an applied framework promoting career-long psychological support services in Swedish handball (CPS-H). The first aim is covered by Study I and II, and the second aim is met in Study III and IV. The dissertation is designed as a collection of four articles with one article per study. Study I focused on a qualitative exploration of career experiences from 18 Swedish professional handball players including major career stages and transitions in their athletic and non-athletic development. The players` accounts were consolidated into the ECM-H describing the context-specific features and pathways throughout the handball career. When developing the ECM-H, gender-specific issues appeared of interest for further investigation. Gender issues were addressed in Study II by re-analyzing the data from Study I. Two composite vignettes were created describing the career pathways of nine male and nine female players. Study III initiated a move from research to practice. Based on the ECM-H, applied sport psychology literature and experiences of the research team led by the first author, the applied framework CPS-H was heuristically developed and validated in three focus groups with end users; professional players, coaches, and sport psychology practitioners. The validated version of the CPS-H is presented with general and career stage-specific recommendations for its implementation among support providers (i.e., where, when, what, who, why, and how of psychological support service). Study IV was designed as an instrumental case study for testing a part of the CPS-H framework. More specifically, the mastery career stage. A career assistance program (CAP) named Life as a professional handball player was developed for, implemented with, and evaluated by Swedish League team. The program included eight workshops dealing with various aspects of the players` athletic and non-athletic life (e.g., performance, training, lifestyle, recovery, future planning), together with crisis-related issues (e.g., coping with uncertainty). These workshops were delivered by the first author during 12 weeks of a competitive season. The mixed-methods evaluation revealed a perceived improvement in players` personal coping resources (e.g., increased awareness) and a decrease in their fatigue and stress. This Project contributes to the athlete career sport psychology discourse and the emerging athlete mental health discourse by presenting the ECM-H and CPS-H frameworks, and the CAP Life as a professional handball player, grounded in the cultural context of Swedish handball. The frameworks and CAP can serve as inspiration for future research and practice, informed by a cultural praxis. The Project shows the usefulness of working as a scientist-practitioner and establishing theory-researchpractice-context links for the promotion of culturally informed implications, and supports the work of facilitating a holistic understanding of athletes` striving for healthy, successful, and long-lasting careers in sport and life.